The Multifaceted Influence of Financial Literacy and Education on SME Financing Decisions in Different Economic Contexts - Ciptawan Ciptawan (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
This research delved into the multifaceted impact of financial literacy and education on Small and Medium-sized Enterprises (SMEs) financing decisions across diverse economic contexts. A systematic literature review examined 280 papers from top-tier